Commedia dell'arte in crossroads territory: the king of hell becomes Saci. - Kodi, Douglas (2022)
This article will elaborate the idea of a Commedia dell'arte spirit, synthesized in the Harlequin mask from its origin in the historical phenomenon and its diabolical myth. To expose the reflection in a practical way, it is crossed with the concept of crossroad by Leda Maria Martins (1995, 2003) that understands Brazil as a territory of amalgamation of cultures. To provide practical support, the character/mask Saci - and the origin of Sacy Pererê - from the play Aconteceu no Brasil enquanto o ônibus não vem do grupo Arte da Comédia (Curitiba-PR) will be referred to as a possible analogue of Harlequin, and the relations of the grotesque that are inherent to both the theater style and the masks.